Dietary Reference Intakes: A Risk Assessment Model for Establishing Upper Intake Levels for Nutrients - Institute of Medicine (The National Academies Press, 1998)
The model for risk assessment of nutrients used to develop tolerable upper intake levels (ULs) is one of the key elements of the developing framework for Dietary Reference Intakes (DRIs). DRIs are dietary reference values for the intake of nutrients and food components by Americans and Canadians. The U.S. National Academy of Sciences recently released two reports in the series (IOM, 1997, 1998). The overall project is a comprehensive effort undertaken by the Standing Committee on the Scientific Evaluation of Dietary Reference Intakes (DRI Committee) of the Food and Nutrition Board (FNB), Institute of Medicine, National Academy of Sciences in the United States, with active involvement of Health Canada. The DRI project is the result of significant discussion from 1991 to 1996 by the FNB regarding how to approach the growing concern that one set of quantitative estimates of recommended intakes, the Recommended Dietary Allowances (RDAs), was scientifically inappropriate to be used as the basis for many of the uses to which it had come to be applied.

Dietary Reference Intakes for Thiamin, Riboflavin, Niacin, Vitamin B6, Folate, Vitamin B12, Pantothenic Acid, Biotin, and Choline - Institute of Medicine (The National Academies Press, 1998)
Since 1941, Recommended Dietary Allowances (RDAs) has been recognized as the most authoritative source of information on nutrient levels for healthy people. Since publication of the 10th edition in 1989, there has been rising awareness of the impact of nutrition on chronic disease. In light of new research findings and a growing public focus on nutrition and health, the expert panel responsible for formulation RDAs reviewed and expanded its approach2014the result: Dietary Reference Intakes. This new series of references greatly extends the scope and application of previous nutrient guidelines. For each nutrient the book presents what is known about how the nutrient functions in the human body, what the best method is to determine its requirements, which factors (caffeine or exercise, for example) may affect how it works, and how the nutrient may be related to chronic disease. This volume of the series presents information about thiamin, riboflavin, niacin, vitamin B6, folate, vitamin B12, pantothenic acid, biotin, and choline. Based on analysis of nutrient metabolism in humans and data on intakes in the U.S. population, the committee recommends intakes for each age group2014from the first days of life through childhood, sexual maturity, midlife, and the later years. Recommendations for pregnancy and lactation also are made, and the book identifies when intake of a nutrient may be too much. Representing a new paradigm for the nutrition community, Dietary Reference Intakes encompasses: Estimated Average Requirements (EARs). These are used to set Recommended Dietary Allowances. Recommended Dietary Allowances (RDAs). Intakes that meet the RDA are likely to meet the nutrient requirement of nearly all individuals in a life-stage and gender group. Adequate Intakes (AIs). These are used instead of RDAs when an EAR cannot be calculated. Both the RDA and the AI may be used as goals for individual intake. Tolerable Upper Intake Levels (ULs). Intakes below the UL are unlikely to pose risks of adverse health effects in healthy people. This new framework encompasses both essential nutrients and other food components thought to pay a role in health, such as dietary fiber. It incorporates functional endpoints and examines the relationship between dose and response in determining adequacy and the hazards of excess intake for each nutrient.

Dietary Reference Intakes for Vitamin C, Vitamin E, Selenium, and Carotenoids - Institute of Medicine
This volume is the newest release in the authoritative series of quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. Dietary Reference Intakes (DRIs) is the newest framework for an expanded approach developed by U.S. and Canadian scientists. This book discusses in detail the role of vitamin C, vitamin E, selenium, and the carotenoids in human physiology and health. For each nutrient the committee presents what is known about how it functions in the human body, which factors may affect how it works, and how the nutrient may be related to chronic disease. Dietary Reference Intakes provides reference intakes, such as Recommended Dietary Allowances (RDAs), for use in planning nutritionally adequate diets for different groups based on age and gender, along with a new reference intake, the Tolerable Upper Intake Level (UL), designed to assist an individual in knowing how much is \

Dietary Reference Intakes for Calcium, Phosphorus, Magnesium, Vitamin D, and Fluoride - Institute of Medicine (The National Academies Press, 1997)
Since 1941, Recommended Dietary Allowances (RDAs) has been recognized as the most authoritative source of information on nutrient levels for healthy people. Since publication of the 10th edition in 1989, there has been rising awareness of the impact of nutrition on chronic disease. In light of new research findings and a growing public focus on nutrition and health, the expert panel responsible for formulation RDAs reviewed and expanded its approach2014the result: Dietary Reference Intakes. This new series of references greatly extends the scope and application of previous nutrient guidelines. For each nutrient the book presents what is known about how the nutrient functions in the human body, what the best method is to determine its requirements, which factors (caffeine or exercise, for example) may affect how it works, and how the nutrient may be related to chronic disease. The first volume of Dietary Reference Intakes includes calcium, phosphorus, magnesium, vitamin D, and fluoride. The second book in the series presents information about thiamin, riboflavin, niacin, vitamin B6, folate, vitamin B12, pantothenic acid, biotin, and choline. Based on analysis of nutrient metabolism in humans and data on intakes in the U.S. population, the committee recommends intakes for each age group2014from the first days of life through childhood, sexual maturity, midlife, and the later years. Recommendations for pregnancy and lactation also are made, and the book identifies when intake of a nutrient may be too much. Representing a new paradigm for the nutrition community, Dietary Reference Intakes encompasses: Estimated Average Requirements (EARs). These are used to set Recommended Dietary Allowances. Recommended Dietary Allowances (RDAs). Intakes that meet the RDA are likely to meet the nutrient requirement of nearly all individuals in a life-stage and gender group. Adequate Intakes (AIs). These are used instead of RDAs when an EAR cannot be calculated. Both the RDA and the AI may be used as goals for individual intake. Tolerable Upper Intake Levels (ULs). Intakes below the UL are unlikely to pose risks of adverse health effects in healthy people. This new framework encompasses both essential nutrients and other food components thought to pay a role in health, such as dietary fiber. It incorporates functional endpoints and examines the relationship between dose and response in determining adequacy and the hazards of excess intake for each nutrient.

Dietary Reference Intakes: Proposed Definition of Dietary Fiber - Institute of Medicine (The National Academies Press, 2001)
The current situation regarding labeling and defining dietary fiber in the United States and many other countries is arbitrary due to its reliance on analytical methods as opposed to an accurate definition that includes its role in health. Without an accurate definition, compounds can be designed or isolated and concentrated using the currently available methods, without necessarily providing beneficial health effects. Other compounds can be developed that are nondigestible and provide beneficial health effects, yet do not meet the current U.S. definition based on analytical methods. For the above reasons, the Food and Nutrition Board, under the oversight of the Standing Committee on the Scientific Evaluation of Dietary Reference Intakes, assembled a Panel on the Definition of Dietary Fiber to develop a proposed definition(s) of dietary fiber. This Panel held three meetings and a workshop.

Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate - Institute of Medicine (The National Academies Press, 2005)
Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate The Dietary Reference Intakes (DRIs) are quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. This new report, the sixth in a series of reports presenting dietary reference values for the intakes of nutrients by Americans and Canadians, establishes nutrient recommendations on water, potassium, and salt for health maintenance and the reduction of chronic disease risk. Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate discusses in detail the role of water, potassium, salt, chloride, and sulfate in human physiology and health. The major findings in this book include the establishment of Adequate Intakes for total water (drinking water, beverages, and food), potassium, sodium, and chloride and the establishment of Tolerable Upper Intake levels for sodium and chloride. The book makes research recommendations for information needed to advance the understanding of human requirements for water and electrolytes, as well as adverse effects associated with the intake of excessive amounts of water, sodium, chloride, potassium, and sulfate. This book will be an invaluable reference for nutritionists, nutrition researchers, and food manufacturers.

Dietary Reference Intakes: Applications in Dietary Planning - Institute of Medicine (The National Academies Press, 2003)
The Dietary Reference Intakes (DRIs) are quantitative estimates of nutrient intakes to be used for planning and assessing diets for apparently healthy people. This volume is the second of two reports in the DRI series aimed at providing specific guidance on the appropriate uses of the DRIs. The first report provided guidance on appropriate methods for using DRIs in dietary assessment. This volume builds on the statistical foundations of the assessment report to provide specific guidance on how to use the appropriate DRIs in planning diets for individuals and for groups. Dietary planning, whether for an individual or a group, involves developing a diet that is nutritionally adequate without being excessive. The planning goal for individuals is to achieve recommended and adequate nutrient intakes using food-based guides. For group planning, the report presents a new approach based on considering the entire distribution of usual nutrient intakes rather than focusing on the mean intake of the group. The report stresses that dietary planning using the DRIs is a cyclical activity that involves assessment, planning, implementation, and reassessment. Nutrition and public health researchers, dietitians and nutritionists responsible for the education of the next generation of practitioners, and government professionals involved in the development and implementation of national diet and health assessments, public education efforts and food assistance programs will find this volume indispensable for setting intake goals for individuals and groups.

Dietary Reference Intakes for Energy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The Dietary Reference Intakes (DRIs) are a set of reference values that encompass a safe range of intake and provide recommended nutrient intakes for the United States and Canada. The DRIs for energy are used widely to provide guidance for maintaining energy balance on both an individual and group level. U.S. and Canadian governments asked the National Academies to convene an expert committee to examine available evidence and provide updated Estimated Energy Requirements (EERs) for their populations. The resulting report presents EER equations that provide a baseline for dietary planners and assessors who are estimating energy needs and monitoring energy balance to enhance the general health of individuals and populations.

Dietary Reference Intakes: Applications in Dietary Assessment - Institute of Medicine
Since 1994 the Institute of Medicine's Food and Nutrition Board has been involved in developing an expanded approach to developing dietary reference standards. This approach, the Dietary Reference Intakes (DRIs), provides a set of four nutrient-based reference values designed to replace the Recommended Dietary Allowances (RDAs) in the United States and the Recommended Nutrient Intakes (RNIs) in Canada. These reference values include Estimated Average Requirement (EAR), Recommended Dietary Allowance (RDA), Adequate Intake (AI), and Tolerable Upper Intake Level (UL). To date, several volumes in this series have been published. This new book, Applications in Dietary Assessment, provides guidance to nutrition and health research professionals on the application of the new DRIs. It represents both a \

An Updated Measure of Poverty: (Re)Drawing the Line - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
An accurate measure of poverty is necessary to fully understand how the economy is performing across all segments of the population and to assess the effects of government policies on communities and families. In addition, poverty statistics are essential in determining the size and composition of the population whose basic needs are going unmet and to help society target resources to address those needs. An Updated Measure of Poverty: (Re)Drawing the Line recommends updating the methodology used by the Census Bureau to calculate the Supplemental Poverty Measure (SPM) to reflect household basic needs. This report recommends that the more comprehensive SPM replace the current Official Poverty Measure as the primary statistical measure of poverty the Census Bureau uses. The report assesses the strengths and weaknesses of the SPM and provides recommendations for updating its methodology and expanding its use in recognition of the needs of most American families such as medical care, childcare, and housing costs.

Facing the Reality of Drug-Resistant Tuberculosis in India: Challenges and Potential Solutions: Summary of a Joint Workshop by the Institute of Medicine, the Indian National Science Academy, and the Indian Council of Medical Research - Institute of Medicine (The National Academies Press, 2012)
An estimated 8.8 million people fell ill with tuberculosis (TB) in 2010 and 1.4 million died from the disease. Although antibiotics to treat TB were developed in the 1950s and are effective against a majority of TB cases, resistance to these antibiotics has emerged over the years, resulting in the growing spread of multidrug-resistant (MDR) TB. Due to challenges in timely and accurate diagnosis of drug-resistant TB, length and tolerability of treatment regimens, and expense of second-line anti-TB drugs, effectively controlling the disease requires complex public health interventions. The IOM Forum on Drug Discovery, Development, and Translation held three international workshops to gather information from local experts around the world on the threat of drug resistant TB and how the challenges it presents can be met. Workshops were held in South Africa and Russia in 2010. The third workshop was held April 18-19, 2011, in New Delhi, India, in collaboration with the Indian National Science Academy and the Indian Council of Medical Research. The aim of the workshop was to highlight key challenges to controlling the spread of drug-resistant strains of TB in India and to discuss strategies for advancing and integrating local and international efforts to prevent and treat drug-resistant TB. This document summarizes the workshop.

The New Profile of Drug-Resistant Tuberculosis in Russia: A Global and Local Perspective: Summary of a Joint Workshop by the Institute of Medicine and the Russian Academy of Medical Science - Institute of Medicine (The National Academies Press, 2011)
An estimated 2 billion people, one third of the global population, are infected with Mycobacterium tuberculosis, the bacterium that causes tuberculosis. Spread through the air, this infectious disease killed 1.7 million in 2009, and is the leading killer of people with HIV. Tuberculosis (TB) is also a disease of poverty–the vast majority of tuberculosis deaths occur in the developing world. Exacerbating the devastation caused by TB is the growing threat of drug-resistant forms of the disease in many parts of the world. Drug-resistant tuberculosis presents a number of significant challenges in terms of controlling its spread, diagnosing patients quickly and accurately, and using drugs to treat patients effectively. In Russia in recent decades, the rise of these strains of TB, resistant to standard antibiotic treatment, has been exacerbated by the occurrence of social, political, and economic upheavals. The Institute of Medicine (IOM) Forum on Drug Discovery, Development, and Translation, in conjunction with the Russian Academy of Medical Sciences held a workshop to discuss ways to fight the growing threat of drug-resistant TB. The New Profile of Drug-Resistant Tuberculosis in Russia: A Global and Local Perspective: Summary of a Joint Workshop presents information from experts on the nature of this threat and how it can be addressed by exploring various treatment and diagnostic options.

The Global Crisis of Drug-Resistant Tuberculosis and Leadership of China and the BRICS: Challenges and Opportunities: Summary of a Joint Workshop by the Institute of Medicine and the Institute of Microbiology, Chinese Academy of Sciences - Institute of Medicine (The National Academies Press, 2014)
Multidrug-resistant tuberculosis (TB) is caused by bacteria resistant to isoniazid and rifampicin, the two most effective first-line anti-TB drugs, originally developed and introduced in the 1950 and 1960s. Since 2008, the Forum on Drug Discovery, Development, and Translation of the Institute of Medicine has hosted or co-hosted six domestic and international workshops addressing the global crisis of drug-resistant TB, with special attention to the BRICS countries - Brazil, Russia, India, China, and South Africa. The Global Crisis of Drug-Resistant Tuberculosis and Leadership of China and the BRICS is the summary of a workshop convened to address the current status of drug-resistant TB globally and in China. This report considers lessons learned from high burden countries; highlights global challenges to controlling the spread of drug-resistant strains; and discusses innovative strategies to advance and harmonize local and international efforts to prevent and treat drug-resistant TB. Additionally, the report examines the problem of MDR TB and emergent TB strains that are potentially untreatable with drugs available and considers the critical leadership role of the BRICS countries in addressing the threats and opportunities in drug-resistant TB.

Forum on Drug Discovery, Development, and Translation: Annual Report 2009 - Institute of Medicine
The year 2009 saw continued upheaval in the scientific and business landscape of drug development. With the new administration came a renewed emphasis on science, as expressed by President Obama in a speech he delivered at the National Academy of Sciences, \

The Emerging Threat of Drug-Resistant Tuberculosis in Southern Africa: Global and Local Challenges and Solutions: Summary of a Joint Workshop by the Institute of Medicine and the Academy of Science of South Africa - Institute of Medicine (The National Academies Press, 2011)
Tuberculosis (TB) kills approximately 4,500 people worldwide every day. While most cases of TB can be treated with antibiotics, some strains have developed drug resistance that makes their treatment more expensive, more toxic and less effective for the patient. The IOM Forum on Drug Discovery, Development, and Translation and the Academy of Science of South Africa held a workshop to discuss ways to fight the growing threat of drug-resistant TB.

Addressing the Threat of Drug-Resistant Tuberculosis: A Realistic Assessment of the Challenge: Workshop Summary - Institute of Medicine (The National Academies Press, 2009)
Tuberculosis is one of the leading causes of death in the world today, with 4,500 people dying from the disease every day. Many cases of TB can be cured by available antibiotics, but some TB is resistant to multiple drugs–a major and growing threat worldwide. The Institute of Medicine's Forum on Drug Discovery, Development, and Translation hosted a workshop on November 5, 2008, to address the mounting concern of drug-resistant TB. The session brought together a wide range of international experts to discuss what is known and not known about this growing threat, and to explore possible solutions.

Breakthrough Business Models: Drug Development for Rare and Neglected Diseases and Individualized Therapies: Workshop Summary - Institute of Medicine
The process for developing new drug and biologic products is extraordinarily expensive and time-consuming. Although large pharmaceutical companies may be able to afford the cost of development because they can expect a large return on investment, organizations developing drugs to treat rare and neglected diseases are unable to rely on such returns. On June 23, 2008, the Institute of Medicine's Forum on Drug Discovery, Development, and Translation held a public workshop, \

Preventing HIV Infection Among Injecting Drug Users in High-Risk Countries: An Assessment of the Evidence - Institute of Medicine (The National Academies Press, 2007)
Drug dependence is a complex, chronic, relapsing condition that is often accompanied by severe health, psychological, economic, legal, and social consequences. Injecting drug users are particularly vulnerable to HIV and other bloodborne infections (such as hepatitis C) as a result of sharing contaminated injecting equipment. All drug-dependent individuals, including injecting drug users (IDUs), may be at increased risk of HIV infection because of high-risk sexual behaviors. There are an estimated 13.2 million injecting drug users (IDUs) world-wide201478 percent of whom live in developing or transitional countries. The sharing of contaminated injecting equipment has become a major driving force of the global AIDS epidemic and is the primary mode of HIV transmission in many countries. In some cases, epidemics initially fueled by the sharing of contaminated injecting equipment are spreading through sexual transmission from IDUs to non-injecting populations, and through perinatal transmission to newborns. Reversing the rise of HIV infections among IDUs has thus become an urgent global public health challenge2014one that remains largely unmet. In response to this challenge, the Institute of Medicine convened a public workshop in Geneva in December 2005 to gather information from experts on IDU-driven HIV epidemics in the most affected regions of the world with an emphasis on countries throughout Eastern Europe, the Commonwealth of Independent States, and significant parts of Asia. Experts from other regions also provided information on their experiences in preventing HIV infection among IDUs. This report provides a summary of the workshop discussions. Preventing HIV Infection among Injecting Drug Users in High Risk Countries describes the evidence on the intermediate outcomes of drug-related risk and sex-related risk prior to examining the impact on HIV transmission. This report focuses on programs that are designed to prevent the transmission of HIV among injecting drug users. These programs range from efforts to curtail non-medical drug use to those that encourage reduction in high-risk behavior among drug users. Although the report focuses on HIV prevention for IDUs in high-risk countries, the Committee considered evidence from countries around the world. The findings and recommendations of this report are also applicable to countries where injecting drug use is not the primary driver, but in which injection drug use is nevertheless associated with significant HIV transmission.

Adverse Drug Event Reporting: The Roles of Consumers and Health-Care Professionals: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
Recent concerns about the unexpected adverse effects of marketed drugs, such as COX-2 (cyclooxygenase-2) inhibitors or specific statins, raise concerns not only about reporting these events during premarket studies, but also about the responsibility for ongoing surveillance of drugs once they are on the market. Sometimes serious adverse drug reactions are fully appreciated only after a drug has been on the market for years. Therefore, when a drug is approved and released to the market, large numbers of patients will be exposed before all the potential adverse effects have been identified and thoroughly studied. Currently, there is no clearly defined process for addressing safety questions about drugs after premarketing research has occurred. In November 2005, the Institute of Medicine's Forum on Drug Discovery, Development, and Translation convened a workshop to explore issues associated with the reporting of ADEs. The workshop addressed the following questions: How can ADEs be effectively identified, particularly when the adverse effects are rare? How can the direct, causal effects of drugs be distinguished from simple associations? How can health-care professionals and their patients' aid in the identification of drug-related adverse events? How can knowledge of ADEs be more effectively used in clinical practice? Adverse Drug Event Reporting reviews current sources of information on adverse drug events, including the FDA's MedWatch program and the AERS, institutional review boards, and the CMS. This report considers the ways that consumers and advocacy groups can be involved in reporting adverse events, and discusses drug interactions, problems with current databases for capturing and evaluating interactions, and difficulties in communicating information about adverse drug interactions. This report also describes new requirements for information contained on drug labels and how labels can be used to communicate information about risks and drug interactions to consumers and practitioners.